1992
DOI: 10.1080/10826079208018855
|View full text |Cite
|
Sign up to set email alerts
|

Use of High Ionic Strength Buffers for the Separation of Proteins and Peptides with Capillary Electrophoresis

Abstract: Journal of Liquid ChromatographyPublication details, including instructions for authors and subscription information: ABSTRACTThe use of high ionic strength buffers with capillary electrophoresis in untreated fused silica capillaries is demonstrated for the separation of proteins and peptides. Short, small i.d. (20-25 pm) capillaries are useful as a quick screening tool for protein analysis. Electropherograms of standard proteins run from pH 5.0 to 10.0 in 0.5 M sodium phosphate buffers suggest that at these h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 18 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…Over the years, various strategies have been developed to diminish or eliminate interactions between analyte and FS-capillary wall, alter the EOF to achieve more rapid separation, or improve the repeatability [25]. These strategies involve the separations performed in extreme pH values [26] and in high ionic strength BGEs [27], addition of amines [28] or zwitterions [29] in BGEs, and use of coated capillaries [30][31][32][33][34][35] running buffer usually requires long analysis time due to the following two reasons. One is that low pH values would result in low EOF when using bare-FS capillary [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various strategies have been developed to diminish or eliminate interactions between analyte and FS-capillary wall, alter the EOF to achieve more rapid separation, or improve the repeatability [25]. These strategies involve the separations performed in extreme pH values [26] and in high ionic strength BGEs [27], addition of amines [28] or zwitterions [29] in BGEs, and use of coated capillaries [30][31][32][33][34][35] running buffer usually requires long analysis time due to the following two reasons. One is that low pH values would result in low EOF when using bare-FS capillary [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In CE, a commonly solution to this is a use of a low pH [11] or high ionic strength buffer, sometimes with an organic modifier [12,13], and a covalent (static) [14] or dynamic coating [14][15][16][17] modification of the capillary surface. Recently, there have been many reviews on this subject [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, DOI-CE is practically limited to charged analytes, and only when the EOF was not completely suppressed the determination of neutral compounds would be possible which would be moved by the low EOF together with ionic compounds with a higher and opposite sign electrophoretic mobility than the EOF. In order to allow the electrophoretic mobility of the analyte to dominate, some researchers have reduced the EOF by increasing the ionic strength of the buffer [34,35]. Brechtel et al [36] first reported the use of high-charged metal salts for this purpose.…”
Section: Foundations and Requirements Of Doi-cementioning
confidence: 99%